Dual role of the receptor Tom20 in specificity and efficiency of protein import into mitochondria - Yamamoto, Hayashi; Itoh, Nobuka; Kawano, Shin; Yatsukawa, Yoh-ichi; Momose, Takaki; Makio, Tadashi; Matsunaga, Mayumi; Yokota, Mihoko; Esaki, Masatoshi; Shodai, Toshihiro; Kohda, Daisuke; Aiken Hobbs, Alyson E; et al. (Proceedings of the National Academy of Sciences - PNAS, 2011)
Mitochondria import most of their resident proteins from the cytosol, and the import receptor Tom20 of the outer-membrane translocator TOM40 complex plays an essential role in specificity of mitochondrial protein import. Here we analyzed the effects of Tom20 binding on NMR spectra of a long mitochondrial presequence and found that it contains two distinct Tom20-binding elements. In vitro import and cross-linking experiments revealed that, although the N-terminal Tom20-binding element is essential for targeting to mitochondria, the C-terminal element increases efficiency of protein import in the step prior to translocation across the inner membrane. Therefore Tom20 has a dual role in protein import into mitochondria: recognition of the targeting signal in the presequence and tethering the presequence to the TOM40 complex to increase import efficiency.